Alignment of PrEP adherence and HIV exposure risk among pregnant and postpartum women in Lilongwe, Malawi - Anna M. Leone; Friday Saidi; Lauren A. Graybill; Qinghua Li; Twambilile Phanga; Feng-Chang Lin; Twaambo E. Hamoonga; K. Rivet Amico; Wilbroad Mutale; Benjamin H. Chi (PLoS ONE, 2025)
Objective When measured continuously, adherence to HIV pre-exposure prophylaxis (PrEP) is consistently low in studies of pregnant and postpartum women. We investigated how PrEP adherence aligned with HIV exposure risk. Methods We conducted a trial of a PrEP adherence support intervention in Lilongwe, Malawi. Pregnant women who met eligibility criteria for PrEP had visits at three and six months following enrollment. At each visit, HIV exposure risk was categorized as low or moderate/high (i.e., higher) risk based on an algorithm. PrEP adherence was measured via tenofovir concentrations, with functional adherence defined at levels consistent with ≥4 doses/week. HIV exposure risk and PrEP adherence were classified as either aligned (i.e., higher HIV risk/PrEP adherence, low HIV risk/PrEP non-adherence) or not aligned (i.e., higher HIV risk/PrEP non-adherence, low HIV risk/PrEP adherence). Probability differences (PD) were used to estimate the effect of the PrEP adherence intervention on aligned PrEP adherence. Results 164 women were included in the analysis. HIV exposure risk was higher for 81 participants (49%) at three months and 89 (54%) at six months. PrEP adherence was low at three months (34%) and at six months (29%). Aligned PrEP adherence was observed in 89 (54%) participants at three months and 83 (51%) at six months. 62% at higher HIV exposure risk were not aligned at month three, which increased to 68% at month six. The probability of aligned PrEP adherence was greater among those randomized to the intervention than those receiving standard of care at three months (PD:15.7%; 95%CI:0.8%, 30.6%). This was also evident in analyses that considered women with high HIV risk but low adherence. Conclusion Alignment of PrEP adherence with HIV exposure risk was dynamic. PrEP adherence should be considered in the context of evolving HIV exposure risk during pregnancy and postpartum, with greater emphasis on periods of elevated HIV risk exposure.